SOX-9 as a prognostic marker in gastric adenocarcinoma - Efe Yetişgin; Aysun Gökçe; Kutsal Doğan (Biomolecules & Biomedicine)
SRY-box transcription factor 9 (SOX9) has been reported to be overexpressed in a wide variety of gastrointestinal malignancies. While its role has been studied in gastric cancer (GC), the results remain conflicting. This study aimed to evaluate the relationship between SOX9 immunohistochemistry results and the pathological and clinical characteristics of gastric adenocarcinoma, assessing its potential as a prognostic marker. Gastric tissue samples from 150 patients with gastric cancer were included in the study. Tissue sections were stained using an anti-SOX9 antibody, and relevant data were retrospectively collected from digital records. Immunostaining results were scored based on the proportion and intensity of stained nuclei throughout the tumor. A final immunostaining score was calculated by multiplying the SOX9 intensity score by the proportion score. Strong SOX9 nuclear staining was observed in 68 patients (45.3%), while moderate staining was seen in 60 patients (40%). SOX9 nuclear staining was absent in three patients (2%). A final SOX9 immunostaining score of ≥10, classified as high expression, was identified in 60 patients (40%). Patients with higher SOX9 expression or strong intensity scores exhibited significantly larger tumor sizes, higher rates of perineural and vascular invasion, more advanced T or lymph node staging, and greater likelihoods of lymphatic or distant metastases compared to those with lower SOX9 expression or intensity scores (all P < 0.05). These findings suggest that SOX9 staining intensity and expression are associated with increased tumor malignancy and disease progression. Therefore, SOX9 may serve as a prognostic pathological indicator in GC patients.